Violência entre parceiros íntimos e suas relações com os gatilhos de agressão - Paiva, Tamyres Tomaz (2018)
The general Aggression model (GAM) employs three central factors to understand aggressive behavior: personal and situational factors, internal trajectories or routes, and behavioral response factors. These factors are seen as social needs, whereby a threat to internal balance is enough, aggressive or violent responses are soon stimulated. GAM conceptualizes intimate partner violence (IPV) as an intentional behavior that causes physical, sexual, psychological, and behavioral harm. From this definition, 7 studies were distributed in 6 articles. The data were analyzed by the statistical software IBM SPSS Statistics and the AMOS, both version 21 and the R language. The first article aimed to analyze the correlation and prediction of the behavioral factors of the violence with the personal factors and the assertive behavior. A total of 305 residents of the city of Grande João Pessoa, aged between 18 and 56 years (M = 25.29, SD = 7.32) participated. The results showed that the factors of violence were correlated with gender, personality (pleasantness, emotional stability and openness to experiences) and values (interactive, normative, suprapersonal, existence and achievement). In addition, it has been found through regression and mediation that these factors can have direct as indirect effects on the behaviors suffered from intimate partner violence. The second article, of a psychometric nature, consisted in the adaptation and validation of a measure that was of behaviors practiced of violence between intimate partners. They were divided into two studies. The first group had 280 respondents from the State of Paraíba, aged between 18 and 58 years (M = 26.83, SD = 6.93). From the analysis of the main components, there were 3 factors (psychological, physical abuse and behavioral control), showing internal consistency. The second study included 218 participants, the majority of the northeast region (52.3%), aged 18-60 years (M = 28.59; SD = 6.95), and consisted of a confirmatory analysis presenting good indexes of adjustments to the model, presenting a shorter and more parsimonious version of the scale. The third article consisted of the construction and validation of a scale of sexual violence, an aggressor version, divided into two studies. The first study had the same participants in study two of article 2, presenting from the analysis of the main components the existence of 1 factor and satisfactory internal consistency. In the second study, there were 203 resident respondents from the State of Paraíba, aged 18-60 years (M = 21.62; SD = 5.25), to verify the confirmatory analysis. The mentioned instruments of article 2 and 3 presented satisfactory psychometric properties, presenting construct validity through the factorial analyzes. The fourth article aimed to analyze the correlation and prediction of personal factors in violence behaviors. The results showed a correlation and prediction between personality factors, human values and attitudes implied by intimate partner violence. And the fifth article, aimed at analyzing the correlation and prediction of violence (physical, psychological, behavioral and sexual abuse) with the personal factor (personality), situational factor (alcohol use) and route (affections). Participants were 411 respondents, the majority resident in Paraíba State (69.7%), aged between 18 and 60 years (M = 25.22, SD = 7.10). The results showed a significant correlation between violence with pleasantness, emotional stability, conscientiousness, narcissism, Machiavellianism, psychopathy, positive and negative affects and the frequency of alcohol consumption. But only the negative affects, Machiavellianism and psychopathy explained the violence between intimate partners. Therefore, the objective of this dissertation was fulfilled, and the results of the studies should be weighed, as they present some limitations. Further research is encouraged in order to replicate the data.